The Use of Surveying and Photogrammetric Court Evidence in the Usucaption Procedures for Proving the Acquisition of the Ownership of Real Estate - Cienciała, Agnieszka; Florek-Paszkowski, Ryszard (Geomatics and Environmental Engineering, 2019)
Fulfilling the required prerequisites for acquisitive prescription (usucaption) such as uninterrupted possession and the lapse of time results in the acquisition of ownership. Both, in the stage of examining the case in respect of fulfilling the prerequisites for acquisitive prescription as well as in the stage of adjudicating in court proceedings, contemporary and archive urveying and photogrammetric evidence plays a vital role. There are situations when the socalled "œacquisitive prescription map", prepared by a licensed land surveyor, showing the area being the subject of the petition and the state of cadastral boundaries as of the day of acquiring the ownership right, is necessary. The aim of this paper is the analysis of the applicability of present and archival aerial photos, maps, especially cadastral orthophotomaps and other documents gathered in the state geodetic and cartographic resource as a proof of holding an immovable, justifying the data of acquiring the right by acquisitive prescription and showing the scope of possession. In fact, the combined analysis of all the above-mentioned evidence accessible for a given area gives complete information about a property being in its entirety or in part a matter of proceedings for ascertaining the acquisition of the ownership of a real property by acquisitive prescription. Moreover, this publication describes some of the problems encountered in the professional practice of court experts during preparation of cquisitive prescription maps.